Developing a core outcome set for the health outcomes for children and adults with congenital oesophageal atresia and/or tracheo-oesophageal fistula: OCELOT task group study protocol - Nigel J Hall; Anna-may Long; Nick Lansdale; Sebastian King; Lucy Bray; Tom Kovesi; Alex Adams; Jonathan Ducey; Paul Cullis; Shireen A Nah; Lin Yin Ong; Victoria Gray; et al. (BMJ Publishing Group, 2024)
Introduction Heterogeneity in reported outcomes of infants with oesophageal atresia (OA) with or without tracheo-oesophageal fistula (TOF) prevents effective data pooling. Core outcome sets (COS) have been developed for many conditions to standardise outcome reporting, facilitate meta-analysis and improve the relevance of research for patients and families. Our aim is to develop an internationally-agreed, comprehensive COS for OA-TOF, relevant from birth through to transition and adulthood.Methods and analysis A long list of outcomes will be generated using (1) a systematic review of existing studies on OA-TOF and (2) qualitative research with children (patients), adults (patients) and families involving focus groups, semistructured interviews and self-reported outcome activity packs. A two-phase Delphi survey will then be completed by four key stakeholder groups: (1) patients (paediatric and adult); (2) families; (3) healthcare professionals; and (4) researchers. Phase I will include stakeholders individually rating the importance and relevance of each long-listed outcome using a 9-point Likert scale, with the option to suggest additional outcomes not already included. During phase II, stakeholders will review summarised results from phase I relative to their own initial score and then will be asked to rescore the outcome based on this information. Responses from phase II will be summarised using descriptive statistics and a predefined definition of consensus for inclusion or exclusion of outcomes. Following the Delphi process, stakeholder experts will be invited to review data at a consensus meeting and agree on a COS for OA-TOF.Ethics and dissemination Ethical approval was sought through the Health Research Authority via the Integrated Research Application System, registration no. 297026. However, approval was deemed not to be required, so study sponsorship and oversight were provided by Alder Hey Children's NHS Foundation Trust. The study has been prospectively registered with the COMET Initiative. The study will be published in an open access forum.